EV Battery Degradation - Rodrigues, Rui (2022)
Rodrigues, R., Albuquerque, V., Ferreira, J. C., & Dias, M. S. (2022). EV Battery Degradation: A Data Mining Approach. In A. L. Martins, J. C. Ferreira, & A. Kocian (Eds.), Intelligent Transport Systems: 5th EAI International Conference, INTSYS 2021, Proceedings (pp. 177-191). (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST; Vol. 426 LNICST). Springer Science and Business Media Deutschland GmbH. https://doi.org/10.1007/978-3-030-97603-3_13 ------------------- Funding Information: This study was performed in the scope of ISCTE collaboration with Santos e Vale, who financed the research. Publisher Copyright: © 2022, ICST Institute for Computer Sciences, Social Informatics and Telecommunications Engineering.